The impact of multimorbidity on grip strength in adults age 50 and older: Data from the health and retirement survey (HRS). (September 2017) - Yorke, Amy M.; Curtis, Amy B.; Shoemaker, Michael; Vangsnes, Eric
Highlights: Multimorbidity, defined as having two or more chronic disease, is experienced by three out of four Americans 65 years and older and is associated with limitations in activities of daily living. Limitations in activity of daily living can occur secondary to decreases in muscle strength. Grip strength is simple to complete and is an overall measure of muscle strength. Adults with chronic diseases demonstrate an incremental decrease in grip strength with multimorbidity, and is especially noted once a person has three or more chronic diseases. Grip strength may be utilized in the care of a patient with multimorbidity, as a measure not related to a specific disease, but as an assessment of overall strength that considers several diseases. Abstract: Background: Multimorbidity, the presence of two or more chronic diseases, is a public health concern. The measurement of grip strength has been proposed as a measure of overall body strength and is reliable and easy to measure. The purpose of this study was to investigate the relationship between the number of chronic diseases and common co-occurring chronic diseases with grip strength. Methods: A cross-sectional analysis was conducted of 5877 respondents (2744 = male, 3103 = female) from the 2008 Health and Retirement Study (HRS) who completed grip strength measurements (kg). Results: As the number of chronic diseases increased, an incremental decrease in grip strength occurred and became more pronounced with ≥3 chronic diseases present ( b  = 3.1, 95% CI = 2.3–3.9, p < 0.001). No statistically significant relationship was identified between specific chronic diseases (except for stroke) and grip strength. Conclusion: Multimorbidity has a statistically significant negative relationship on grip strength. Grip strength should be considered as a physical performance measure to incorporate into the care of patients with multimorbidity.